Facebook's role in crisis response. Issue 10 (14th September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – This paper notes that, while the public represented on Facebook applies distinct crisis frames in comparison to conventional sources, its frame-setting power is limited. It discovers that it is rather the news media that influences the crisis framing in social media. This paper concludes that the role of the public represented on Facebook appears marginal in comparison to news media that remain a major force in the discursive negotiation of a corporate crisis. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.